Inventory Management System Using QR Code on Android a Case Study in Computer Engineering Department - Renza Ilhami Rizqi; Nurul Azizah Rohma; Dr. Kittiwan Nimkerdphol (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Inventory management is the practice overseeing and controlling of the ordering, storage and use of components thata company uses in the production of the items it sells. Inventory management has been used as a decision-making incountless firms and has been extensively studied in the academic and corporate spheres. The purposes of inventorysystem are to know the details of the items including code, name, condition, location of items and the year ofpurchase. It is also to make easy for manage the item. Usually, creating inventory list can be done two ways eithermanually or computerized. Manually inventorying is usually written data with handwriting on the data books. It hasmany disadvantages. One of them is when the admin staff input the data, it is prone to be typographical errors. Herein the Computer Engineering Department in Rajamangala University of Technology Thanyaburi (RMUTT) theinventory management still using manual process for inventorying and collect the data of an item. This inventorymanagement system will help the process inventorying using web-based application and also mobile application forcollecting data information. Quick Response (QR) Code technology as a unique tagging solution for each item thatstore information from the server through the local network. The implementation of this system for InventoryManagement System could be a solution for manage inventorying process and stored information of inventorythrough QR Code.